1999
DOI: 10.1023/a:1026483823176
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Heterotrimeric GTP-binding proteins, composed of alpha, beta, and gamma subunits, are involved in signal transduction pathways in animal and plant systems. In plants, physiological analyses implicate heterotrimeric G-proteins in ion channel regulation, light signaling, and hormone and pathogen responses. However, only one class of plant G alpha genes has been identified to date. We have cloned a novel gene, 'Arabidopsis thaliana extra-large GTP-binding protein' (AtXLG1). AtXLG1 appears to be a member of a smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(27 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…The number of studies on XLGs grew slowly since the first plant extra-large G protein was reported (Lee and Assmann, 1999), however, in the last 2 years, interest in these atypical signal components has surged relatively (Chakravorty et al, 2015; Maruta et al, 2015; Liang et al, 2016; Urano et al, 2016; Wang et al, 2017). The general role for XLG proteins centers on stress responsiveness but we still lack a good understanding of the mechanism and while the subcellular localization has been reported, there has been conflicting results with no explanation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of studies on XLGs grew slowly since the first plant extra-large G protein was reported (Lee and Assmann, 1999), however, in the last 2 years, interest in these atypical signal components has surged relatively (Chakravorty et al, 2015; Maruta et al, 2015; Liang et al, 2016; Urano et al, 2016; Wang et al, 2017). The general role for XLG proteins centers on stress responsiveness but we still lack a good understanding of the mechanism and while the subcellular localization has been reported, there has been conflicting results with no explanation.…”
Section: Resultsmentioning
confidence: 99%
“…The N-terminal region of XLGs contains a nuclear localization signal (NLS) and at least XLG3 in this family encodes a functional nuclear export signal (NES) (Chakravorty et al, 2015). Whether or not XLGs bind guanine nucleotides is unclear but the evidence to date indicate that if they do, the mode is different from the canonical Gα subunit (Lee and Assmann, 1999; Heo et al, 2012). In vitro studies indicate that XLGs bind the Gβγ dimer but do so unlike the canonical Gα subunit (Maruta et al, 2015) and possibly do so independently of nucleotide binding (Urano et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…3). There are three extra-large GTP binding proteins that have a carboxyl-terminal half with significant homology to Gα proteins but with molecular masses much greater than 54 kDa which also do not likely bind GTP given that the conserved GTP-binding pocket lacks critical residues (Lee and Assmann 1999; Ding et al 2008; Assmann 2002). A suitable alternative is that GPA1 and AS/7 antibodies recognize in WT seedlings a different version of the GPA1 protein which could result from a cry1-mediated post-translational modification.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the CaaX motif of AGG3 is not conserved in some other plants. XLG, a plant-specific Gα-like protein, has a nuclear localization signal (NLS), cysteine-rich region and a C-terminal Gα-like domain [57]. The Gα-like sequence does not conserve some of the residues for hydrolysing GTP or for interacting with Gβγ [57,58].…”
Section: Regulatory System Of Animal and Plant Heterotrimeric G Proteinsmentioning
confidence: 99%
“…XLG, a plant-specific Gα-like protein, has a nuclear localization signal (NLS), cysteine-rich region and a C-terminal Gα-like domain [57]. The Gα-like sequence does not conserve some of the residues for hydrolysing GTP or for interacting with Gβγ [57,58]. AtRGS1 is a 7TM protein harbouring a RGS domain; the 7TM region is essential for localizing RGS1 to the plasma membrane [52].…”
Section: Regulatory System Of Animal and Plant Heterotrimeric G Proteinsmentioning
confidence: 99%